THE RELATHIONSHIP OF VITAL SIGNS WITH GCS OF STROKE PATIENTS - Akhmad Fauzi; Prestasianita Putri; Alfid Tri Afandi (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2022)
ABSTRACT Stroke is a clinical syndrome of sudden onset, rapidly progressive, in the form of focal or global neurologic deficits. A stroke occurs because there is a narrowing or rupture of a blood vessel in the brain. Resulting in an increase in intracranial pressure so that the hypothalamus sends a signal to raise the body temperature and compensate for an increase in BP, pulse, glycemic, RR. If you don't get treatment, the patient is unconscious (decreased GCS) and death occurs. This study aims to identify the relationship of vital signs with GCS of stroke patients. The independent variable in this study was vital signs, while the dependent variable was GCS in stroke patients. This study has 124 respondents using a sampling technique that is purposive sampling. The design of this study used an analytic type of observation with a cross sectional approach. The most influential vital signs with GCS of stroke patients in the ER are body temperature with a p-value = 0.000 (p<0.05) with a Beta value of 0.489. From this study, it can be explained that there is a relationship between vital signs and GCS. Stroke patients in the ER at Bina Sehat Hospital Jemberwith body temperature as vital signs that are most related to GCS of stroke patients. Keyword: Vital signs, GCS, Stroke